PURPOSE AND ORIGIN OF ENVIRONMENTAL SCIENCE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Dear reader, this article provides information about the origin, directions of Environmental Science and scientists who have made scientific research by contributing to its origin.